2023
DOI: 10.1177/23259671221145733
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Scaffold Application in Arthroscopic Reconstruction of Osteochondral Lesions of the Talus With Autologous Cancellous Bone Grafts

Abstract: Background: Single-step all-arthroscopic techniques have gained popularity recently in the treatment of osteochondral lesions of the talus (OLT). Concomitant subchondral bone defects led surgeons to add autologous bone grafting to the surgical procedures. Collagen scaffolds have been used widely for stabilization of the reconstruction and regeneration of the articular surface. Purpose: To compare single-step all-arthroscopic treatment of OLT consisting of debridement, microfracture, autologous bone grafting, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
0
0
Order By: Relevance
“…Significant heterogeneity was observed in VAS scores between the two groups (I 2 = 81.8%, P = 0.004). Subsequent sensitivity analysis revealed that the meta-analysis results were influenced by 2 studies [ 34 , 36 ]. Consequently, a decision was made to abandon the meta-analysis and only perform descriptive analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Significant heterogeneity was observed in VAS scores between the two groups (I 2 = 81.8%, P = 0.004). Subsequent sensitivity analysis revealed that the meta-analysis results were influenced by 2 studies [ 34 , 36 ]. Consequently, a decision was made to abandon the meta-analysis and only perform descriptive analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…According to the recommendations by the International Consensus Group on Cartilage Repair of the Ankle [38], the use of additional scaffolds may be considered for OLTs with a lesion size of >1 cm 2 . However, several studies have reported that application of the collagen membrane to the BMS or autologous bone grafting did not provide better clinical outcomes [39,40]. Therefore, the efficacy of the present surgical procedure augmented with collagen membrane or biologics needs to be assessed in future studies.…”
Section: Discussionmentioning
confidence: 97%